2023
DOI: 10.3389/fnins.2022.1068498
|View full text |Cite
|
Sign up to set email alerts
|

Activated microglia and neuroinflammation as a pathogenic mechanism in Leigh syndrome

Abstract: Neuroinflammation is one of the main mechanisms leading to neuronal death and dysfunction in neurodegenerative diseases. The role of microglia as primary mediators of inflammation is unclear in Leigh syndrome (LS) patients. This study aims to elucidate the role of microglia in LS progression by a detailed multipronged analysis of LS neuropathology, mouse and human induced pluripotent stem cells models of Leigh syndrome. We described brain pathology in three cases of Leigh syndrome and performed immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…One limitation of our current study is the use of a small molecule approach that has a systemic effect and is not able to answer the cell-type specificity of our treatment, but it may facilitate the translation to clinical therapeutics. Treatment options for LS patients are very limited; however, promising pre-clinical studies using the same germline Ndufs4 −/− mouse model have identified potential new therapies to alleviate LS pathologies, including rapamycin [31], chronic hypoxia [32], supplementation of NAD + [24], and microglial ablation [33]. Chronic hypoxia decreased toxic oxygen metabolites and has been shown to improve survival, body weight, body temperature, behavior, neuropathology, disease biomarkers, and brain NAD + concentration in LS mice [34].…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our current study is the use of a small molecule approach that has a systemic effect and is not able to answer the cell-type specificity of our treatment, but it may facilitate the translation to clinical therapeutics. Treatment options for LS patients are very limited; however, promising pre-clinical studies using the same germline Ndufs4 −/− mouse model have identified potential new therapies to alleviate LS pathologies, including rapamycin [31], chronic hypoxia [32], supplementation of NAD + [24], and microglial ablation [33]. Chronic hypoxia decreased toxic oxygen metabolites and has been shown to improve survival, body weight, body temperature, behavior, neuropathology, disease biomarkers, and brain NAD + concentration in LS mice [34].…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, we and others described that decreasing the neuroimmune response by depleting microglial cells has beneficial effects in Ndufs4 KO mice [ 17 , 18 , 37 ]. In this study, we wanted to assess whether a chronic induction of a neuroinflammatory state prior to neuropathology onset could affect the pathology of Ndufs4 KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…The brain pathology in LS patients shows white matter vacuolization, increased vascularity and gliosis, microglial expansion, and increased IL-6 levels in the cerebellum and brainstem in NDUFS4 -/- mice, and neuroinflammation is indicated in LS patients’ brains 27 . The antioxidative and anti-ferroptotic effects of apomorphine and its derivatives need to be evaluated for pathological alterations when administered to the brain tissue.…”
Section: Discussionmentioning
confidence: 99%